2021
DOI: 10.3390/v13060951
|View full text |Cite
|
Sign up to set email alerts
|

Novel Biomarkers of Hepatitis B Virus and Their Use in Chronic Hepatitis B Patient Management

Abstract: Even though an approved vaccine for hepatitis B virus (HBV) is available and widely used, over 257 million individuals worldwide are living with chronic hepatitis B (CHB) who require monitoring of treatment response, viral activity, and disease progression to reduce their risk of HBV-related liver disease. There is currently a lack of predictive markers to guide clinical management and to allow treatment cessation with reduced risk of viral reactivation. Novel HBV biomarkers are in development in an effort to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 170 publications
0
30
0
1
Order By: Relevance
“…Recent studies have shown that HBV RNA is detectable in the serum of chronic hepatitis B patients (treated and untreated) as well as in acute infection [ 12 , 13 ]. The HBV RNA in serum includes primarily full-length encapsidated pgRNA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have shown that HBV RNA is detectable in the serum of chronic hepatitis B patients (treated and untreated) as well as in acute infection [ 12 , 13 ]. The HBV RNA in serum includes primarily full-length encapsidated pgRNA.…”
Section: Resultsmentioning
confidence: 99%
“…Serum HBV pgRNA has emerged as a new biomarker reflecting the levels and activity of intrahepatic HBV covalently closed circular DNA (cccDNA) [ 13 ]. HBV pgRNA can be released into the serum within enveloped virions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…for nucleic acid amplification and detection) likely contribute to variability in quantitative molecular test results, which can be up to 100-fold using various WHO international standards [24][25][26]. The availability of an international standard is mandatory to properly compare results obtained from different studies [6,7,25]. The establishment of such a standard would enable a better interpretation of results generated with tests targeting different parts of the HBV genome.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, new biomarkers for liver diseases, based on post-translational modifications by glycosylation, have been attracting attention. In addition to tumor markers for HCC, the HBV genotype, HBV genomic mutations, host genome mutations in HBV-infected hepatocytes and gene expression patterns of HCC cells could be candidate biomarkers for HBV-related HCC [ 5 , 6 , 7 ]. Novel technologies including these biomarkers have the potential to predict the prognosis of HCC patients.…”
Section: Introductionmentioning
confidence: 99%